Influence of carboxymethylation on the surface physical–chemical properties of glucuronoxylan and arabinoxylan films. Issue 12 (9th January 2015) - Velkova, Nena; Doliška, Aleš; Fras Zemljič, Lidija; Vesel, Alenka; Saake, Bodo; Strnad, Simona
Abstract : Xylans were carboxymethylated in order to increase their anionic nature and thus tune their surface free energy (SFE) and hydrophilicity, which are of crucial importance in the majority of special applications. Fourier transform infrared spectroscopy and polyelectrolyte titration results confirmed the successful carboxymethylation of the xylan samples. The main aim of this study was to investigate the influences of carboxymethylation of glucuronoxylan and arabinoxylans on the surface physical and chemical properties of the films made from them. Films were prepared by the casting method, and their surface morphologies were analyzed by atomic force microscopy. The surface chemical compositions of the films were investigated using X‐ray photoelectron spectroscopy, and their influences on SFE, i.e., Lifshitz–van der Waals and electron donor and acceptor contributions, were determined using goniometry. The introduction of ∼2 mmol/g of carboxyl groups into the glucuronoxylan or arabinoxylan molecular structures had a significant influence on the chemical and physical surface properties of the prepared films. Higher amounts of the carboxyl group present on the films' surfaces and higher surface roughness contributed to a significant increase (by 270%) in the electron donor component of SFE and to 40% improvements in the hydrophilicities of the films' surfaces. POLYM. ENG. SCI., 55:2706–2713, 2015. © 2015 Society of Plastics Engineers